Ovarian Tissue Vitrification as a Method for Ovarian Preservation in Women with Cancer: an Analysis of Granulose Cell Apoptosis - Wiweko, Budi; Andriyana, Huthia; Aulia, Achmad (Indonesian Socety of Obstetrics and Gynecology, 2016)
Objective: To obtain the effective method of ovarian function preservation with granulose cell apoptosis assessment. Ovarian tissue vitrification became a method for ovarian function preservation in women with cancer. This technique can be done anytime without delay on cancer therapy both in prepubertal and unmarried patient. It can also store many primordial follicles. Ovarian tissue vitrification study is still limited to animal test and there are no data about apoptosis assessment after ovarian vitrification in human ovary. Method: This quasi experimental study was held in Department of Obstetrics and Gynecology Faculty of Medicine University of Indonesia - Dr. Cipto Mangunkusumo General Hospital and Fatmawati Hospital Jakarta from March 2012 to May 2015. Ovaries from thirteen women between 31 and 37 years old who underwent oophorectomy with gynecological indication were examined. Result: There was no morphological difference between follicles from fresh and warmed-vitrified ovaries. The mean protein Bax expression on the fresh ovaries assessed in the form of H-score was 1.66 (SD 0.14) compared with 1.68 (SD 0.13) on the warmedvitrified group (p=0.165). The mean protein Bcl-2 expression on the fresh ovaries examined in the form of H-score was 1.73 (SD 0.10) compared with 1.71 (SD 0.10) on the warmed-vitrified group (p=0.068). Conclusion: Ovarian tissue vitrification does not affect the Bax and Bcl-2 expression on human ovary. [Indones J Obstet Gynecol 2016; 4-2: 88-92] Keywords: apoptosis, bax, Bcl-2, ovarian tissue vitrification